THE ROLE OF WAROPEN TRIBAL CHIEF RISEI SAYATI IN THE PROCESS OF RESOLVING CUSTOMARY LAND DISPUTES IN WAROPEN REGENCY - Tanati, Daniel; Yoseph Palenewen, James (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
The research, entitled "The Role of Waropen Tribal Chief Risei Sayati in the Customary Land Dispute Resolution Process in Waropen Regency," aims to determine the role of Waropen Tribal Chief Risei Sayati in the customary land dispute resolution process in Waropen Regency and to identify the obstacles encountered by Waropen Tribal Chief Risei Sayati in the customary land dispute resolution process in Waropen Regency. The method used in this research is empirical juridical, namely identifying and conceptualizing law as a real and functional social institution in the real life system. The output of this research is to contribute to legal thought and knowledge for the people of Waropen Regency regarding the role of Waropen Tribal Chief Risei Sayati in the customary land dispute resolution process. This will enable the local indigenous community to seek the assistance of the Tribal Chief as a leader and neutral party in resolving the dispute.